Posts intertextuais: um estudo de links nos blogs Luis Nassif online, Conversa afiada e o Biscoito fino e a massa - Dalmaso, Silvana Copetti (2011)
A digital writing was incorporated in to web journalistics practices and to our everyday surfing for digital spaces. The links became part of the websites and blogs reading. Observe how these links, as mechanisms of intertextuality, organize themselves in posts blogs concerning to their disposition, direction and function in approaching of a specific event is the aim of this research. In order to do this, we constructed a theoretical trajectory toward to the discussion of blogs as spaces of digital writing that was formed by multilinearity, dispersion and textual openness, besides the intertextuality which constitutes the digital media language. In this context, the hypertext elements that structure the messages, links and their different uses present themselves as paths of intertexts and intertextuality organizers. Our conceptual overview also discussed the relations of blog with journalism starting from the contribution of Digital Journalism in Databases for the development of dynamic products that exploit content aggregation and memory until the specificities that shape blogs like personalization and subjectivity in textual style, the network content filtering function and the critical position in relation to media. The methodology used to study the posts links was content analysis with the creation of categories based on typologies already developed and the adaptation of others. Our empirical study was composed by 26 posts of Luis Nassif Online, Conversa Afiada and O Biscoio Fino e a Massa blogs. These posts were published between 21 and 28 October 2010 and refer to an alleged aggression against the ex-candidate of presidential election, José Serra, in an event that was popularly known as bolinha de papel case. Besides other results, the links mapping showed that the most of the linked texts of the posts regarded to external materials and the predominant functions of these links were highlight the references of used contents and complement the information exposed in the posts writings.